Metagenomic next-generation sequencing could play a pivotal role in validating the diagnosis of invasive mold disease of the central nervous system - Wei, Erhu; Niu, Jiechao; Zhang, Mengjiao; Zhang, Yu; Yan, Kunli; Fang, Xiao; Ma, Wei; Xie, Lei; Jia, Peisheng; Wang, Huaili (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Invasive mold diseases of the central nervous (CNS IMD) system are exceedingly rare disorders, characterized by nonspecific clinical symptoms. This results in significant diagnostic challenges, often leading to delayed diagnosis and the risk of misdiagnosis for patients. Metagenomic Next-Generation Sequencing (mNGS) holds significant importance for the diagnosis of infectious diseases, especially in the rapid and accurate identification of rare and difficult-to-culture pathogens. Therefore, this study aims to explore the clinical characteristics of invasive mold disease of CNS IMD in children and assess the effectiveness of mNGS technology in diagnosing CNS IMD. Methods: Three pediatric patients diagnosed with Invasive mold disease brain abscess and treated in the Pediatric Intensive Care Unit (PICU) of the First Affiliated Hospital of Zhengzhou University from January 2020 to December 2023 were selected for this study. Results: Case 1, a 6-year-old girl, was admitted to the hospital with "acute liver failure." During her hospital stay, she developed fever, irritability, and seizures. CSF mNGS testing resulted in a negative outcome. Multiple brain abscesses were drained, and Aspergillus fumigatus was detected in pus culture and mNGS. The condition gradually improved after treatment with voriconazole combined with caspofungin. Case 2, a 3-year-old girl, was admitted with "acute B-lymphoblastic leukemia." During induction chemotherapy, she developed fever and seizures. Aspergillus fumigatus was detected in the intracranial abscess fluid by mNGS, and the condition gradually improved after treatment with voriconazole combined with caspofungin, followed by "right-sided brain abscess drainage surgery." Case 3, a 7-year-old girl, showed lethargy, fever, and right-sided limb weakness during the pending chemotherapy period for acute B-lymphoblastic leukemia. Rhizomucor miehei and Rhizomucor pusillus was detected in the cerebrospinal fluid by mNGS. The condition gradually improved after treatment with amphotericin B combined with posaconazole. After a six-month follow-up postdischarge, the three patients improved without residual neurological sequelae, and the primary diseases were in complete remission. Conclusion: The clinical manifestations of CNS IMD lack specificity. Early mNGS can assist in identifying the pathogen, providing a basis for definitive diagnosis. Combined surgical treatment when necessary can help improve prognosis.